Noble Humbug? Hard and soft laws on clinical placebo use - Mélina Richard; Mélina Richard; Manuela Ganz; Lena Dominique Hornstein; Bohdan Stehlik; Mélanie Levy; Charlotte R. Blease; Marco Annoni; Bernice S. Elger; Jens Gaab (Frontiers in Psychology)
Despite the widespread historical and contemporary use of placebos in medicine, legal regulations addressing their administration remain limited in many countries. This paper examines the legal landscape of clinical placebo use, focusing on key jurisdictions such as France, Germany, Switzerland, the United Kingdom, and the United States. Given the ethical and legal complexities surrounding placebo use, a critical assessment of existing regulatory frameworks is essential. This study employs a multidisciplinary approach, analyzing both binding laws (“hard laws”) and non-binding principles (“soft laws”) related to placebo administration. Data were collected from legal statutes, health institution guidelines, and professional medical codes to map the regulatory environment governing placebos in different legal systems. The results indicate significant variations in how placebos are addressed legally. For instance in Germany and the UK, no specific laws regulate placebo use, but statutes on informed consent implicitly cover their administration. In the United States, the American Medical Association provides ethical guidelines permitting placebo use under strict conditions emphasizing patient welfare and transparency. Across all examined jurisdictions, unauthorized placebo use may lead to legal consequences such as medical fraud allegations or violations of patient rights. These findings highlight the need for explicit regulatory guidelines to ensure that placebo use adheres to ethical and legal standards. The growing acceptance of open-label placebos (OLPs), which demonstrate efficacy without deception, presents a potential avenue for aligning legal frameworks with evolving medical practices. Future regulatory developments should address the ethical and legal challenges associated with placebos, ensuring patient autonomy and informed consent remain central to their use in clinical practice.